The Effects of Shock Advertising on Purchase Intentions and Behavior of Cigarettes in Collectivistic Culture - PURWANTO, Edi; UTAMA, Cindy; WIJAYA, Betania (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
Then objective of the research area is to investigate: (1) The effect of the customers purchasing intention on purchasing behavior; (2) The moderating effect of Indonesian collectivist culture on the relationship between shock advertising and the customers purchase intention; and (3) The moderating effect of Indonesian collectivist culture on the relationship between shock advertising and the customers purchase behavior. In the study we collected quantitative data by convenience distributing questionnaires to the respondents are Indonesians in Jakarta, but not limited to Jakarta citizens only. This study uses non-probability sampling technique and the number of respondents or research sample is 250 respondents. The findings, firstly, the results of this research prove that there is a positive and significant effect of purchase intentions and purchase behavior towards cigarette products. Secondly, the use of shock advertising in order to reduce the number of smokers in Indonesia is not really effective, and thirdly, this research also found that there are no moderation affects of the collectivism culture towards the relationship between shock advertising with the purchase behavior to buy cigarettes in Indonesia. This paper shows that shock advertising is not have effect on purchase intentions and purchase behavior towards cigarette products in the collectivist culture, like as Indonesia.